Mechanical properties and fracture behavior of sandstone similar materials with different joint positions and thicknesses based on triaxial testing and PFC simulation - Wei Jing; Bingpeng Lu; Laiwang Jing; Rencai Jin (Archives of Civil Engineering)
The mechanical properties and failure characteristics of joined rocks have an important impact on the disaster prevention of underground engineering and the sustainable development of mineral resources. The effects of confining pressure, joint location, and joint thickness on the mechanical properties of rock-like specimens under triaxial test have been studied. Furthermore, using the "DFN-age" function of PFC numerical simulation, the stress characteristics, and failure characteristics of rock specimens under different confining pressure, joint location and joint thickness are analyzed. The research results indicate that as the thickness of the joint increases and the joint position approaches the center of the specimen, the compressive strength of the specimen decreases. As the confining pressure increases, the compressive strength increases and failure modes of rock like specimens with different joint types also tend to be similar. The specimens manifest complex shear-tensile composite failures. In addition, the initiation cracks and main control cracks at the joint terminus can be classified as reverse tensile wing cracks, reverse shear cracks, shear cracks and tensile wing cracks. When the joint thickness of the specimen is 1.0 mm and the distance from the joint position to the center of the specimen is 10–20 mm, the crack evolution characteristics and stress distribution law of the specimen will undergo a transformation.